General Considerations on Dance Movement Therapy and its applications in social field - Rodríguez Jiménez, Rosa María; Dueso Pla, Elena (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2016)
General aspects of the Dance Movement Therapy (DMT) are here exposed along with the historical origins and its evolution in recent decades. DMT is a model of psychotherapeutic intervention, which shares some features with other creative therapies. Non–verbal expressions and creative moment within a therapeutic relationship are inherent and particular characteristics of DMT. The article emphasizes its interdisciplinary dimension and the increasing applications in social and educational fields, to promote and enhance health. Finally, the current status of the profession in Spain framed in the European context is presented.